Search for single production of scalar leptoquarks in p(p)over-bar collisions decaying into muons and quarks with the D0 detector - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2007)
We report on a search for second generation leptoquarks (LQ2) which decay into a muon plus quark in p over(p, ̄) collisions at a center-of-mass energy of sqrt(s) = 1.96   TeV in the D0 detector using an integrated luminosity of about 300 pb-1. No evidence for a leptoquark signal is observed and an upper bound on the product of the cross section for single leptoquark production times branching fraction β into a quark and a muon was determined for second generation scalar leptoquarks as a function of the leptoquark mass. This result has been combined with a previously published D0 search for leptoquark pair production to obtain leptoquark mass limits as a function of the leptoquark-muon-quark coupling, λ. Assuming λ = 1, lower limits on the mass of a second generation scalar leptoquark coupling to a u quark and a muon are mLQ2 > 274   GeV and mLQ2 > 226   GeV for β = 1 and β = 1 / 2, respectively. © 2007 Elsevier B.V. All rights reserved.